Pure wild forest reindeer (Rangifer tarandus fennicus) or hybrids? A whole-genome sequencing approach to solve the taxonomical status - Weldenegodguad, Melak; Niemi, Milla; Mykrä-Pohja, Sakari; Pokharel, Kisun; Hamama, Tuula-Marjatta; Paasivaara, Antti; Kantanen, Juha (Springer Nature, 2024)
In Finland, the geographic distribution of domestic reindeer (Rangifer tarandus tarandus) and Finnish wild forest reindeer (Rangifer tarandus fennicus) partly overlap in the vicinity of the southern border of the reindeer herding area. Additionally, domestic reindeer are occasionally kept as pets within the distribution range of the wild forest reindeer. Hybridisation of these two subspecies is one of the major threats for the wild forest reindeer population. Concerns about potential hybridisation served as the catalyst also for this study, which we aimed to clarify the taxonomic status of presumed wild forest reindeer individuals intended as founder individuals for a reintroduction project. To do this, we resequenced genomes of four Rangifer tarandus individuals with unknown taxonomical status and investigated their ancestries by comparing the genomic data with the existing resequenced data of the Finnish domestic reindeer and Finnish wild forest reindeer. The genetic relationship investigations indicated that all individuals we analysed were pure wild forest reindeer, making them suitable as founder individuals for the reintroduction project. Thus, our study provided critical knowledge for practical conservation action, where it was essential to recognise each individual’s origin. In the future, it will also offer novel insights into the spread of native wild forest reindeer to new geographic regions in Finland. For subsequent studies, additional resequenced genomic data of Rangifer individuals will be needed to develop an ancestry information marker panel of single nucleotide polymorphisms for rapid and cost-effective identification of hybrid individuals of these subspecies.
Keywords: metsäpeura; poro; genomiikka; sekvensointi; risteymät (biologia); forest reindeer; domestic reindeer; genomics; sequencing; admixture